Quality Control Evaluation of the Microbial Contamination of Bottled Drinking Water and House Hold Reverse Osmosis Water in Tripoli, Libya - Omar Rbeida; Shahrazad Eteer (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Access to clean and safe water is essential for human life. Among the quality control requirements of drinkable water are the microbiological monitoring tests to prevent any microbial contamination. Bottled water is generally considered to be safe for use by people. However, several reports have reported that bottled water does not always meet the accepted standards. House hold Reverse Osmosis (RO) stations are commonly used in houses which purified the supply water using membrane filters, it has high efficiency in removing dissolved salts, chemicals, impurities and microorganisms from the water. This study aimed to assess the microbiological quality of RO water samples and some domestic bottled waters marketed in Tripoli-Libya. Methods. About 9 samples of different bottled drinking water and 18 samples of RO drinking water were collected from different parts in Tripoli. Results. The microbiological analysis tests of this study showed that the total bacterial counts of bottled waters and one sample of RO water were below 10 CFU/100 ml. A total of 16 RO samples had a total of the bacterial count in the range between 10 and 300,000 CFU/100 ml and one sample was found with a bacterial count of more than 300,000 CFU/100 ml. However, total coliform bacteria, yeast and mold were not detected in all bottled and RO water samples. Conclusion. The tested domestic bottled waters sold in markets and shops in Tripoli have bacteriological contents within the accepted ranges based on WHO standards, whereas almost all the RO samples have high bacterial count that can be risky to human health. Accordingly, the public should be aware of the proper use of RO stations and monitoring the validity of filters in order to be efficient to produce safe water that is free of microbial and chemical contamination